Who Benefits from Labor Market Regulations? Chile 1960-1998 - Montenegro, Claudio E.; Pagés, Carmen (World Bank, Washington, DC, 2014)
Economists have examined the impact of labor market regulations on the level of employment. But there are many reasons to suspect that the impact of regulations differs across types of workers. In this paper the authors take advantage of the unusually large variance in labor policy in Chile to examine how different labor market regulations affect the distribution of employment and the employment rates across age, gender, and skill levels. To this effect, they use a sample of repeated cross-section household surveys spanning the period 1960-98 and measures of the evolution of job security provisions and minimum wages across time. The results suggest large distribution effects. The authors find that employment security provisions and minimum wages reduce the share of youth and unskilled employment as well as their employment rates. They also find large effects on the distribution of employment between women and men.